The Encouragement and Constraint of Distributed Leadership via Education Policy Reform in Nova Scotia, Canada: A Delicate Balancing Act - Williams, Monica; Young, David C. (International Journal of Education Policy and Leadership, 2022)
This article examines how recent policy reforms in Nova Scotia, Canada, encouraged and constrained distributed leadership in the provincial public education system. The study found the language of newly enacted legislation and policies encouraged distributed leadership by endorsing collaborative team processes for school improvement and special education/inclusive education. However, distributed leadership was constrained by the elimination of elected school boards, the reduced authority of school advisory councils, the altered duties of educational leaders, and the failure to enact essential supports for distributed leadership. Overall, this analysis found that recent policy reforms strengthened the control of the provincial ministry of education at the expense of local, democratic participation in education. The need for new organizational structures and processes for citizen participation in twenty-first century education was identified.